2012
DOI: 10.1242/jcs.102210
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage migration inhibitory factor (MIF) promotes cell survival and proliferation of neural stem/progenitor cells

Abstract: SummaryIn a previous study, we showed that murine dendritic cells (DCs) can increase the number of neural stem/progenitor cells (NSPCs) in vitro and in vivo. In the present study, we identified macrophage migration inhibitory factor (MIF) as a novel factor that can support the proliferation and/or survival of NSPCs in vitro. MIF is secreted by DCs and NSPCs, and its function in the normal brain remains largely unknown. It was previously shown that in macrophages, MIF binds to a CD74-CD44 complex. In the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
118
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(124 citation statements)
references
References 68 publications
6
118
0
Order By: Relevance
“…We screen several neuronal-and glial cell-(including RG) secreted molecules that might have the potential to induce microglia proliferation. Among them, we concentrated on MIF 38,39 , since it has been consistently shown that this cytokine can modulate myeloid cell proliferation by binding to the CD74 receptor 40 . By in situ hybridization we detected MIF mRNA in germinal niches of the developing cerebral cortex at E12.5, E14.5, E16.5 and E18.5.…”
Section: Resultsmentioning
confidence: 99%
“…We screen several neuronal-and glial cell-(including RG) secreted molecules that might have the potential to induce microglia proliferation. Among them, we concentrated on MIF 38,39 , since it has been consistently shown that this cytokine can modulate myeloid cell proliferation by binding to the CD74 receptor 40 . By in situ hybridization we detected MIF mRNA in germinal niches of the developing cerebral cortex at E12.5, E14.5, E16.5 and E18.5.…”
Section: Resultsmentioning
confidence: 99%
“…MIF is a cancer-related gene that has previously been shown to promote cell survival and proliferation in mouse NSCs (40). Intriguingly, the MIF ( Fig.…”
Section: Btics Expressed Mif and P53mentioning
confidence: 87%
“…MIF is thus a pivotal regulator of atherogenesis and also plaque vulnerability. [10][11][12] MIF is associated with extensive lesion development, 12,13 whereas blocking MIF or its genetic deletion reduces macrophage and T-cell content in atherosclerotic plaques and attenuates atheroprogression in ApoE −/− mice.…”
Section: Circulation Researchmentioning
confidence: 99%
“…[11][12][13][14][15] Because most of these diseases are ameliorated by either genetic deletion of Mif or MIF neutralization, anti-MIF therapies have raised significant clinical interest. MIF levels in plasma are enhanced in patients with acute myocardial infarction and associated with inflammatory markers C-reactive protein and IL-6 and correlate with cardiac necrosis marker troponin I release.…”
Section: Circulation Researchmentioning
confidence: 99%